Current management of adults receiving oral anti-cancer medications: A scoping review. (October 2021) - Richmond, J.P.; Kelly, M.G.; Johnston, A.; Murphy, P.J.; Murphy, A.W.
Abstract: Purpose: Oral anti-cancer medication (OAM) has revolutionised oncology care. Due to their potential toxicities and associated safety challenges ongoing assessment and monitoring is essential; currently generally performed in acute care settings. Internationally there exists a transformative vision to shift patient care from acute to primary care. A nurse-led integrated model of care could be developed for OAM patient management in primary care. The aim of this study was to examine international literature regarding current clinical management practices for assessment and monitoring of patients receiving OAM. Methods: Following PRISMA-ScR guidelines, databases MEDLINE, CINAHL and Web of Science were searched for English studies published between 2010 and 2020 using keywords: assessment, cancer, care, management, oral anticancer medications. Articles were screened and assessed for eligibility. From eligible studies, data were extracted to summarize, collate and make a narrative account of the findings. Results: 2261 papers were reviewed, 14 met inclusion criteria. Three phases of management are reported: 1. Patient treatment plan development; 2. Patient education; 3. Patient monitoring. Within these phases seven specific stages of care were identified broadly representing the patient's journey: (1) treatment decision, (2) prescribing of OAM, (3) OAM dispensing and administration, (4) maximising patient safety (5) ongoing patient assessment (6) patient support (7) communication with other health-care professionals. Conclusions: Despite a paucity of international literature, a dedicated OAM clinic was endorsed as a means to achieve improved care. Nurses and pharmacists were identified as being of particular importance especially in education and ongoing management of patients receiving OAMs. Highlights: There is a paucity of international literature reporting the current management of adults receiving OAMs. A dedicated oral anti-cancer medication clinic is unanimously endorsed as a means to achieve improved care. Nurses and pharmacists were identified as being important for education and the daily management of OAM patient care.